2016
DOI: 10.17795/iji-32788
|View full text |Cite
|
Sign up to set email alerts
|

Infection Control Practices and Program Management in Labor and Delivery Units: A Cross-Sectional Study From Iran

Abstract: Background: Although Iranian women increasingly attend hospitals for childbirth, no information is available on programs and practices related to infection control in labor and delivery units. Objectives: This study aims to investigate infection control program management and midwives' practices in labor and delivery units. Patients and Methods:We analyzed data related to infection control program management and also practices performed by 88 midwives in four labor and delivery units in public hospitals in Zah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The DPI project offered the staff members the opportunity to become more engaged in their practice process as they participated in learning about improving overall health through maternal healthcare interventions and education program services presented during this period at this local hospital. Tabatabaei, Behmanesh, Pour, and Azadeh [14] pointed out essential gaps worth addressing in practice, including insufficiency in hospital infection control plans, unreliable scrutiny of healthcare-related infections, lack of antibiotic stewardship, insufficient written and displayed guidelines and policies, inadequate sterilization and cleansing of equipment, and inadequate hand hygiene. Providing training to healthcare workers was vital to improving infection control standards.…”
Section: Resultsmentioning
confidence: 99%
“…The DPI project offered the staff members the opportunity to become more engaged in their practice process as they participated in learning about improving overall health through maternal healthcare interventions and education program services presented during this period at this local hospital. Tabatabaei, Behmanesh, Pour, and Azadeh [14] pointed out essential gaps worth addressing in practice, including insufficiency in hospital infection control plans, unreliable scrutiny of healthcare-related infections, lack of antibiotic stewardship, insufficient written and displayed guidelines and policies, inadequate sterilization and cleansing of equipment, and inadequate hand hygiene. Providing training to healthcare workers was vital to improving infection control standards.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to neonatal sepsis and perinatal asphyxia is higher in our country neonatal intensive care unit which is the leading cause of neonatal morbidity and mortality in Ethiopia (24)and also due to poor infection prevention in hospitals. In Ethiopia hospitals the infection prevention practice was 52.2% (25) while in settings in which earlier studies have been conducted was 76.2% in India(26) and 70% in Iran (27).And also this nding is higher than the average global prevalence of neonatal thrombocytopenia which is 22-35%(28).This may be due to most of the studies are conducted in developed countries so it lowers the prevalence globally.…”
Section: Neonatal Related Factorsmentioning
confidence: 98%
“…This finding is similar to the findings in a study on IPC in labor and delivery unit in Iran where it was reported that none of the HW made use of eye shield or face mask during similar procedures. [27] This showed that most HW, especially in the maternity units of secondary HF, were highly susceptible to blood borne infections such as hepatitis B, C, and HIV.…”
Section: Ipac Practice Scores (%)mentioning
confidence: 99%